New heat treatment technique (tempering-austempered in single treatment) for matrix transformation and mechanical properties of ductile iron / Bulan Abdullah … [et al.] - Abdullah, Bulan; Jaffar, Ahmed; Rashiddy Wong, Freddawati; Ab Rashid, Amirul; Ramli, Abdullah; Talari, Mahesh Kumar; Syarifuddin Djalil, Syarif Junaidi (Research Management Institute (RMI), 2013)
A new heat treatment process which synthesized using the concepts from Austempered Ductile Cast Iron (ADI), Tempering and Quenching technology. The metallurgy of materials matrix transformation on each sequential cycle with different parameter such as time and temperature will be determine through the mechanical properties of ductile iron. Samples for the testing specimen will produce using the C02 casting. The compositions of samples will be determined by using the spectrometer machine. The heat treatment process consists of Quenching, Austempering and new developed heat treatment process with different parameter such as time and temperature. The new developed heat treatment process will be synthesized using the concepts from Austempered Ductile Cast Iron (ADI) and Quenching technology. The micro structure of specimens will be observed on each sequential cycle of heat treatment process. The chemical information of matrix surface will gain through the energy Dispersive X-Ray spectroscopy (EDX). The hardness, impact (ASTM E23), tensile (TS 138 EN10002-1) and density test were carried out before and after heat treatment process. The fracture surface of the tensile and impact samples will examine under Scanning Electron Microscope (SEM). A treatment process is expected possessed the better mechanical properties compared to conventional heat treatment can be used for the specific application that suite the